Efficacy of Bacillus subtilis for controlling anthracnose in chilli - Thanh, Toan Le; Cong, Vinh Kieu; Sangpueak, Rungthip; Numparditsub, Parichat; Papathoti, Narendra Kumar; Machikowa, Thitiporn; Buensanteai, Kumrai (Agriculture and Natural Resources, 2023)
Importance of the work: Chilli cultivation in Thailand has a problem with anthracnose. Biological control is used to reduce such problems. Objectives: To assess the biocontrol efficacy of Bacillus subtilis against Colletotrichum spp. causing anthracnose in chilli. Materials & Methods: The antagonistic effects were evaluated in vitro of B. subtilis on Colletotrichum spp. and the associated effects on chilli seed growth. In addition, the amount of salicylic acid (SA) and phenolic compounds in chilli plants and B. subtilis efficacy on anthracnose severity of leaves and fruits were assessed under net-house conditions. Results: The results showed that the antagonistic percentage of B. subtilis was approximately 55% and it did not affect germination rates, shoot height or the root length of chilli seedlings. The Bacillus treatment reduction levels of anthracnose severity on chilli leaves and fruits were 86–100% and 49–74%, respectively. In the chilli plants, B. subtilis induced phenolic compound levels to approximately 22 mg per 100 g fresh weight (FW) and 19 mg per 100 g FW in leaves and fruits, respectively. Similarly, the amount of SA increased to 62–65 μg/g FW and 14–17 μg/g FW in chilli leaves and fruits, respectively. Main finding: Application of B. subtilis inhibited anthracnose disease in chilli and could be a safe alternative to harmful chemical usage.